THE COMPREHENSIVE ASSESSMENT OF THE EFFECTIVENESS OF ACTIVITIES AIMED TO CONTROL THE SPREAD OF HIV/TB CO-INFECTION IN NORTH-WEST RUSSIA - Z. M. Zagdyn; E. V. Verbitskaya; E. G. Sokolovich; N. A. Belyakov (Туберкулез и болезни лёгких)
In Russia, the downward trends in tuberculosis transmission are leveled by the growing HIV infection spread. In order to improve the situation, it is necessary to know the strengths and weaknesses of tuberculosis control activities among people living with HIV. The objective of the study: the comprehensive assessment of the effectiveness of activities aimed to control the spread of HIV/TB co-infection in North-West Russia. Subjects and methods. The authors used epidemiological and clinical-diagnostic methods, ranking, correlation analysis, and expert assessment. The epidemiological and clinical analyses were based on the reporting forms of Rosstat on tuberculosis and HIV, data from analytical reports on monitoring visits and data from the questionnaires developed by the authors, for 2007-2017. The correlation between the studied parameters was assessed using Spearman's rank correlation. Results. In North-West Russia, the main tuberculosis control activities among people living with HIV, including logistical support and provision of personnel (Spearman's rank ratio (-0.32177), p < 0.05), a set of preventive measures aimed at the coverage with antiretroviral therapy, preventive treatment and screening for tuberculosis in HIV-positive people (Spearman's rank ratio (-0.03226), p > 0.05) did not provide any statistically significant impact on the spread of HIV/TB co-infection, which indicated of their imperfection and inequality. Conclusion. In the North-West of Russia, the system aimed to control the spread of HIV/TB co-infection requires some optimization.